Variations in Oral Microbiota Composition Are Associated With a Risk of Throat Cancer - Wang, Lili; Yin, Gaofei; Guo, Ying; Zhao, Yaqi; Zhao, Meng; Lai, Yunyun; Sui, Pengcheng; Shi, Taiping; Guo, Wei; Huang, Zhigang (Frontiers in Cellular and Infection Microbiology, 2019)
In this study, a next-generation sequencing strategy on 16S rRNA gene was employed to analyze 70 oral samples from 32 patients with throat cancer, 9 patients with vocal cord polyp and 29 healthy individuals (normal controls). Using this strategy, we demonstrated for the first time that the salivary microbiota of cancer patients were significantly different from those of patients with polyp and healthy individuals. We observed that the beta diversity of the cancer group was divergent from both the normal and polyp groups while alpha-diversity indices such as the Chao1 estimator (P = 8.1e-05), Simpson (P = 0.0045) and Shannon (P = 0.0071) were significantly reduced in cancer patients compared with patients containing polyp and normal healthy individuals. LDA and Kruskal-Wallis test analyses and real-time qPCR verification test revealed that genera Aggregatibacter, Pseudomonas, Bacteroides and Ruminiclostridium were significantly enriched in the throat cancer group compared with the vocal cord polyp and normal control group (score value > 2). Finally, diagnostic models based on putatively important constituent bacteria were constructed with 87.5% accuracy (AUC = 0.875, 95% CI: 0.695–1). In summary, in this study we characterized for the first time the oral microbiota of throat cancer patients without smoking history. We speculate that these results will help in the pathogenic mechanism and early diagnosis of throat cancer.